Mortality and potential life years lost due to external causes: Colombia from 1998 to 2015 - Segura-Cardona, Alejandra; Cardona-Arango, Doris (Universidad y Salud, 2018)
Introduction: The external causes of mortality are constituted as a public health problem which affect young population, have social relevance, are avoidable and their impact is reducible in the long term. Objective: To describe the behavior of mortality due to external causes and the potential years of life lost in the Colombian population from 1998 to 2015. Materials and methods: An analytical study was conducted by using 641,837 death certificates which were classified in four large groups of external mortality: homicide, suicide, traffic accident and other causes. Mortality rates (crude and standardized) were calculated with direct method in three periods of time and potential years of life lost, for each group. Results: The risk of dying from external causes was 81.66 per hundred thousand inhabitants, with a decrease of 47.1% and 37.6 potential years of life lost. For homicide, a rate of 47.3 per hundred thousand inhabitants was recorded, with a reduction of 59.3% and 23 potential years of life lost. Traffic accidents recorded a reduction of 30.3% with a rate of 15.7. Suicide documented less reduction in 18 years of age (9.8%) and an average rate of 5.1. Conclusion: Deaths caused by external causes are priorities when it comes to raising public policies, mainly for the reduction of homicides that are a reflection of the armed conflict and the crime presented in the country, generating the loss of years of productive life for society. It is necessary to outline the perpetrators to focus and intervene the most affected populations.